Multiple endocrine neoplasia–like syndrome in 24 baboons (Papio spp.). Issue 6 (6th September 2018) - Confer, Alexandra; Owston, Michael A.; Kumar, Shyamesh; Dick, Edward J.
Abstract: Multiple endocrine neoplasia (MEN) has not been reported in baboons, but this condition is well described in humans. An internal database was searched for all cases of concurrent endocrine hyperplasia and neoplasia in baboons. Twenty‐four baboons ( Papio spp.) with concurrent endocrine hyperplasia and neoplasia were identified. Twenty‐one baboons had lesions in two endocrine organs, two baboons had lesions in three organs, and one baboon had lesions in four organs. Ten baboons aligned with the MEN1 classification; 14 baboons did not match any current human MEN classification. We report 24 cases of MEN‐like syndrome in baboons. MEN1‐like lesions accounted for nearly half (41%) of the affected animals. Genetic analysis of baboons with MEN‐like syndrome could further elucidate the mechanisms of MEN and support the use of baboons as animal models for human MEN.